Anesthesiological Management of a Patient with Williams Syndrome Undergoing Spine Surgery - Federico Boncagni; Luca Pecora; Vasco Durazzi; Francesco Ventrella (Case Reports in Anesthesiology)
Williams Syndrome (WS) is a complex neurodevelopmental disorder associated with a mutation on chromosome 7. Patients with WS usually display dysmorphic facial and musculoskeletal features, congenital heart diseases, metabolic disturbances and cognitive impairment. Structural cardiovascular abnormalities are present in the majority of the children and may provide a substrate for perioperative Sudden Cardiac Death, as presented by several reports, something that creates a great challenge to the anesthetic conduct. We present the case of a 12-year old girl who required anesthetic care for surgical correction of an acquired kyphoscoliosis. Potential anesthesiological implications of WS are subsequently reviewed.